Diversidade de bactérias, genes de resistência a Quinolonas e abundância do gene intl1 em uma estação de tratamento de esgoto revelada por abordagens de cultivo e metagenômica - Magna Cristina de Paiva (2015)
Quinolones are antimicrobial drugs of great clinical relevance, both in human and veterinary. Among the mechanisms of quinolones resistance, the acquisition of resistance genes (qnr, aac(6)Ib-cr, qepA and OqxAB) mediated by mobile genetic elements is highlighted because of its potential of interspecies dissemination. A wide diversity of bacteria of human, animal and environmental are found in wastewater treatment plants (WWTPs), where horizontal genes transfer is favored. In this study, we investigated the abundance of class 1 integron and bacterial and qnA, qnrB, qnrS and aac(6)Ib-cr genes diversities from raw sewage (RS) and activated sludge (AS) from the WWTP Arrudas, Belo Horizonte MG, using culture-based and metagenomic approaches. Proteobacteria was the dominant phylum of RS and AS communities. Moreover, there were a reduction of Firmicutes and Bacteroidetes enrichment in AS.Operational Taxonomic units (OTUs) related to Neisseria, Acinetobacter and Streptococcus genera were detected, however, there was a reduction of reads in AS. Bacterial cells harboring class 1 integrons were found, but with a lesser proportion in AS. The culture-based approach also revealed that the Proteobacteria phyllum were dominant in both environments, with predominance of Enterobacteriaceae. The most abundant species were Escherichia coli, Morganella morganii and Proteus mirabilis. It should be noted that the E. coli detected were from phylogenetic groups B2 and D. Overall, Enterobacteriaceae isolates from RS were more resistant to quinolones and aminoglycosides than those from AS. Bacteria harboring the aac(6)Ib and its variant cr genes predominated in RS, whereas qnrS were specific from AS. It must be highlighted the first detection of qnrS genes in M. morganii, Providencia rettgeri and Pseudomonas guangdongensis and of aac(6)Ib-cr in Alcaligenes faecalis and P. rettgeri from environment source. It was observed that these genes exhibit low diversity, but the diversity of qnrS genes appear to be wider than aac(6)Ib genes. The molecular analysis of sequences obtained revealed several unprecedented amino acid changes in QnrS and Aac(6)Ib proteins, whose structural implication is not straightforward. The findings of this study warn for the presence of resistant bacteria to quinolones and aminoglycosides from RS and AS and the qnrS, aac(6)Ib and its variant cr genes circulating in these environments, which have the potential interspecies dissemination and may compromise the therapeutic use of these antimicrobials.